Measurements of the atmospheric minor constituents at Syowa Station, Antarctica, in 1986 (abstract) - Fukabori, Masashi; Makino, Yukio; Tanaka, Masayuki; Yamaguchi, Sadao; Yamanouchi, Takashi (National Institute of Polar Research, 1989)
P(論文) Column amounts of the atmospheric minor constituents were measured at Syowa Station, Antarctica, (69 departmental bulletin paper